Five-element inverted-F antenna array for MIMO communications and radio direction finding on mobile terminal - Azremi, Abdullah Al Hadi; Kyro, M.; Ilvonen, J.; Halopainen, J.; Ranvier, S.; Icheln, C.; Vainikainen, P. (Institute of Electrical and Electronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/